2010
DOI: 10.1007/s10165-010-0290-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of tocilizumab for patients with active rheumatoid arthritis refractory to anti-TNF biologics: tocilizumab in combination with methotrexate

Abstract: We retrospectively observed the clinical efficacy and safety of tocilizumab (TCZ) in 74 patients with rheumatoid arthritis (RA) at 13 hospitals, without any restrictions on disease duration or stage, treatment history, and other influencing factors. TCZ was infused by the approved method, and disease activity was evaluated every 4 weeks until week 24 using a joint disease activity score (DAS28). Remission and treatment response were categorised using European League Against Rheumatism (EULAR) definitions. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
0
6
1
3
Order By: Relevance
“…However, differences in other values were not significant (Table 1). In previous reports, in RA patients the continuation of methotrexate resulted in better clinical and/or radiographic outcomes than discontinuation upon starting biologics [17,18]. The difference between the present study groups in the proportions of patients who had used methotrexate was not significant, and the average dosage of methotrexate in the two groups was almost the same.…”
Section: Patients' Characteristicscontrasting
confidence: 64%
“…However, differences in other values were not significant (Table 1). In previous reports, in RA patients the continuation of methotrexate resulted in better clinical and/or radiographic outcomes than discontinuation upon starting biologics [17,18]. The difference between the present study groups in the proportions of patients who had used methotrexate was not significant, and the average dosage of methotrexate in the two groups was almost the same.…”
Section: Patients' Characteristicscontrasting
confidence: 64%
“…The DAS28-ESR-remission rate was 83.3% after four doses (4 months) and all patients achieved a EULAR good-or-moderate response (100%) at the same time point 22. In a second study the DAS28-ESR-remission rate was 55.2% and the EULAR good-or-moderate response rate was 97% after 24 weeks 23. Why these two clinical studies show such remarkably higher response rates than found in previous RCTs and the rates found in our study is unclear.…”
Section: Discussionmentioning
confidence: 84%
“…The efficacy and safety of these two drugs in TNFi naïve patients as well as in patients for whom TNFi have failed has been demonstrated in several randomised controlled clinical trials (RCTs),921 but data on their effectiveness in clinical practice are scarce 22 23. Since clinical registries include patients treated in routine care, they provide a valuable supplement to the RCTs, which typically include strictly selected patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of antidrug antibodies in RA patients who were treated with infliximab is much higher compared with etanercept44 45 and tocilizumab 15 46. Second, the tocilizumab group had a significantly lower percentage of biological-naive patients, which may be associated with a less favourable response to treatment 47 48. In the tocilizumab group, we confirmed that the discontinuation rate due to LOE was numerically lower in the biological-naive patients compared with biological agent non-naive patients (see supplementary figure S3, available online only).…”
Section: Discussionmentioning
confidence: 97%